Thermodynamic analysis of the cogeneration system expansion in a sugar-alcohol factory - Fiomari, Marcelo C.; Mashiba, Marcos H. S.; Campitelli, Flavio M.; Takaki, Alessandro T.; Ramos, Ricardo A. V. (Natl Technical Univ Athens, 2006)
In this work it was performed energetic and exergetic analyses of three thermal plants to assessment a cogeneration system in expansion of a sugar-alcohol factory. The initial configuration considered is constituted by a low pressure steam generator, single stage steam turbines for electricity generation and crusher, shredder and mills with mechanical driving. In the intermediary configuration, the low pressure steam generator was substituted by another which generates steam at higher pressure and higher temperature, the steam turbines for electricity generation were substituted by a multiple stages extraction-condensation turbine and the other steam turbines were maintained. The final configuration consists in the substitution of these last turbines by electrical motors. Thermodynamic analyses were performed to evaluate the equipment and the overall plants efficiencies to permit a comparison among the plants. Besides of this, some important parameters of the sugar-alcohol factories were calculated.
Keywords: thermodynamics; energy; exergy; cogeneration; sugar-alcohol factory